(3GdCfhGQ ajeG jefM UGMH GdNdhI ef GdCSQGQs - (3GdMGJej, GdWGFj, GHf YQHj, eMjj GdOjf, eMeO Hf Ydj Hf eMeO Hf YQHj, J(B638(3g`s ((3MGLj Hf EHQGgje Hf Ydj GdJQGHjs)
(3ChdgG (B:s
(3GdMeO dhGgH GdYbd heHOYg CLHJ SDGdc Gdhdj GdcQjeaj cjajI GdSdhc Edi QH GdYRIaChd eG CHjfg dc habc Gddg cjajI GdSdhc Edjg Ke cjajI GdhUhd hGdhbha Hjf jOjgs
(3BNQgG (B:s
(3hGdhGgH jJYdb Hg OGFeG CHOG adefc adjgd GdYGedhf haj eKd gPG adjJfGaS GdeJfGaShf hGdMeO ddg QH GdYGdejfs
(3efbhdI ef NW GdeUfa GdeDQNI SfI (B781(3g` HHjJ GdebOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 6 / 281s
(3eYLe GdeDdajf(B: 3 / 531s
(3cTa GdXfhf(B: 1 / 168s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs